Quality Culture Component of School under the Office of Primary Educational Service Area in the Northeastern - Khamphusa, Siriporn; Nanthasri, Wanphen; Phengsawat, Waro (Dhammathas Academic Journal, 2022)
The objectives of this study were to examine quality culture component of school under the office of primary educational service area in the northeastern. The researcher proceeded in 4 steps: 1) study the relevant documents on the quality culture component of 18 schools. To synthesize the quality culture component of school. 2) Interview 5 experts 3) study schools with best practices under the office of primary educational service area in the northeastern quality to international standards or management or academic at the national level or northeastern level amount 3 school. And 4) confirm the quality culture component under the office of primary educational service area in the northeastern according to the framework obtained from steps 1-3 by 5 experts. This research was survey research. The tools used in the research were document analysis forms, interview form and questionnaire. Analyze the data by content analysis, mean and standard deviation. The findings were as follows: quality culture component of school under the office of primary educational service area in the northeastern have 5 components which are: 1) quality leadership 2) continuous improvement 3) systematic action 4) personnel development and 5) focus on learners and stakeholders.